Obstetric violence: Series of cases - Oyola-García, Alfredo Enrique (2018)
In order to make visible the probable occurrence of lack of respect and / or mistreatment during access to childbirth care, the search was made for news related to delivery care, denial of delivery care or care not timely birth during 2017 in the search engines Google®, Yahoo®, Altavista®, ProMED® and others. Eight cases were found: 75% in adolescents or young people and three out of four cases occurred in Lima and Callao that would show deficiencies in access to quality birth care and could be the tip of the iceberg of inadequate and dehumanized comprehensive care maternal health   DOI 10.25176/RFMH.v18.n4.1730